1988
DOI: 10.1177/00957984880151010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Proper and Improper Usage of the Comparative Research Framework

Abstract: The comparative research framework, contrasting distinct groups by statistical significance tests, is examined for major epistemological and practical problems inherent in its usage with African-European (Black-White) groups. Three axioms are given regarding the proper and improper usage of this approach in the context of epistemological soundness. Published examples of proper and improper usage are presented. Three kinds of proper usage are identified. And, the intricacy in determining whether a given impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 7 publications
0
54
0
Order By: Relevance
“…In light of the arguments discussed above (Hutchison 1988, Azibo 1988 it is suggested that the interpretation of these statistics is questionable, and they are presented primarily for comparison purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the arguments discussed above (Hutchison 1988, Azibo 1988 it is suggested that the interpretation of these statistics is questionable, and they are presented primarily for comparison purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Criticisms of this stream of research may be grouped into two major categories. First, are questions of a definitional nature (Hutchison 1988, Azibo 1988. Concern is expressed regarding research techniques which divide target populations into two general classifications, the ethnic group of interest, and "others".…”
mentioning
confidence: 99%
“…The comparison by race is compelled by the nepenthe formulation and thereby is epistemologically justified (Azibo, 1988(Azibo, , 2002. Points 2 and 3 together implicate an especial association with psychological dysfunction for the maladaptive defense style.…”
Section: Replicationsmentioning
confidence: 99%
“…An instrument that measures the deep structure of culture or the asili, as articulated in the Africentric conception (e.g., Azibo, 1992a), was administered to an African and a European sample. Predictably, the racial comparison analyses, driven by construct compulsion and thereby appropriate epistemologically (Azibo, 1992b), showed that Africans responded in the Africentric direction greater than Europeans and that Europeans responded in the Eurocentric direction greater than Africans. The Baldwin and Hopkins (1990) study renders as moot and baseless Curtis' observation that "the [Africentric conception] theories.., may require revision .... [since they demand] methodological practices [racial comparisons] that threaten.., the ideological paradigm" (Banks, 1992, pp.…”
Section: Flawsmentioning
confidence: 99%